TEACHING EXPERIENCES IN THE DEVELOPMENT OF THE COMMUNICATION COMPETENCE IN STUDENTS WITH COGNITIVE DISABILITY - Mădălina-Maria VASILIU (National Centre for Policy and Evaluation in Education, 2020)
The current analysis starts from a teacher's experience with cognitively disabled students. In such cases, the management of the teaching-learning process is challenged by the limitations of various activities (generalizations, abstraction or inductive-deductive operations). In these situations, the teacher has to select effective activities for developing the competences in the curriculum. In this context, success could only be obtained if proper attention is given to the individual learning needs of each student. At the same time, an emotional relationship that is based on trust needs to be developed between the teacher and the students and their parents. The communication competence is a priority since it is absolutely necessary for the social integration of students with disabilities as it provides the means to express feelings, needs and views. The challenge to plan adequate teaching strategies is correlated with understanding the child's real issue and its timely solution: the more serious the cognitive disability, the later speech develops and remains at a low level in the adult life, generating difficulties in expressing thought and emotion. If the youngsters experience a false disability triggered by the lack of educational stimulation or if they have an authentic cognitive disability, these students need sustained support. The examples of interventions we present in this paper come from our attempts to best value the intellectual potential of these children and, consequently, to find solutions for a differentiated adaptation to each child's needs by planning competence-oriented creative teaching activities.